PEMBUATAN BIOGAS DENGAN PROSES RUDAD Biogas production by using RUDAD process (Rumen derived anaerobic) - R Sudradjat; Triyanto Triyanto (Jurnal Penelitian Hasil Hutan, 1993)
This experiment deals with anaerobic decomposition of organic materials into biogas and compost materials using the so called RUDAD (Rumen Derived Anaerobic Digestion) process. the inoculum used in the process was ruminantia microbes living in fistula liquid of goat stomach. The predominantly microbes involved were cilliate protozoa, phycomycetes fungi, anaerobic bacteria. substrates used were King grass, city waste and saw dust with and without agitation during the treatments.The Results showed that the highest biogas production was obtained from King grass i.e 1.06 1/d and 1.20 1/d for those without and with agitation treatments respectively. the highest volatile solid reduction was also obtained from King grass with the reduction of 6.4 percent for the process without agliation and 7.4 percent for the agitated treatment. king grass again showed the highest COD reduction, i.e. 2.0 g/g and 2.3 g/g for those without and with agitation, respectively. Either for cellulose and lignin degradation,King grass gave the highest cellulose reduction of 13.2 percent for the process without and 14.5 percent for the process with agitations, while lignin reductions were 1. 8 percent for the first and 0. 6 percent for the second treatments.